The Influence of Digital Culture on Employee Performance with Work Discipline as a Moderating Variable - Hertya Andriani; Desi Ulpa Anggraini; Ishak; Mohamad Yusuf Golam; Sian Linda Lerebulan (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This research is a quantitative research with an explanatory approach, which uses primary research to create hypotheses, test hypotheses, modify hypotheses, and prove the hypotheses that are built. The data used in this study is primary data that the researcher obtained from two hundred and eighty Bank Mandiri employees spread throughout Indonesia. The researcher obtained data from an online questionnaire containing ten questions about digital culture, employee performance, and work discipline. The data that the researcher obtained was analyzed using the smart PLS 4.0 analysis tool. The result of this article shows that the Digital Culture variable can have a positive relationship direction and a significant influence on employee performance. The P-values are positive and below the 0.05 significance level, namely 0.002. These results are in line with research. These results indicate that the better the Digital Culture, the easier it will be for employees to complete tasks and be more successful in completing targets. This, in turn, can improve Employee Performance. In the next row, the Work Discipline variable can moderate the influence of the Digital Culture variable on Employee Performance because the P-values also tend to be positive and below the 0.05 significance level, namely 0.000, smaller than direct testing. Thus, it can be concluded that this article's first and second hypotheses can be accepted and proven.